A rare case of recurrent orbital solitary fibrous tumour with intracranial extension - Ainal Adlin N,; Umi Kalthum Md Noh,; Amizatul Aini S,; Reena Rahayu Md Zain,; Safinaz Mohd Khialdin, (Faculty of Medicine, UKM Medical Centre, 2016)
A 47-year-old lady, presented with progressive proptosis of left eye with deterioration of vision. She had a history of left solitary fibrous tumour and had undergone left frontal craniotomy and orbitotomy in 2004. Surveillance Magnetic resonance imaging (MRI) six years later showed tumour recurrence with intracranial extension. However, she did not follow-up and only presented again 3 years, later. Tumour resection and left exenteration was performed. Histology showed ‘patternless’ pattern of neoplastic cells, and CD34 staining was diffusely positive. Diagnosis of recurrent solitary fibrous tumour with intracranial extension was made.